Designing modular camera bags for outdoor photographers: A human-centered response to visual culture and environmental challenges in Indonesia - Dewi Pitaloka Sari; Hanif Azhar; Bintang Nugraha (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Outdoor photography represents an evolving visual culture practice within Indonesia’s digital society, where mobility, self-expression, and environmental adaptability are increasingly crucial. However, existing photography gear often fails to address the contextual challenges faced by outdoor photographers, particularly in relation to unpredictable tropical weather and the demands of a mobile digital lifestyle. This study responds to this gap by designing a modular camera bag using a Human-Centered Design (HCD) approach. Employing a qualitative case study method with participatory elements, the research integrates interviews, field observations, and questionnaires involving urban outdoor photographers. The design process follows the IDEO Human-Centered Design (HCD) framework, consisting of the stages of Inspiration, Ideation, and Implementation, and is supported by a thematic analysis of field data to derive actionable design insights. The resulting design emphasizes spatial flexibility, weather-resistant materials, and a modular system that promotes sustainability and personalization. Beyond addressing functional requirements, the bag embodies visual identity and reflects how everyday object design can negotiate cultural expressions, environmental adaptation, and digital mobility within Indonesia’s socio-visual landscape.   Fotografi outdoor merupakan praktik yang berkembang dalam masyarakat digital Indonesia, yang ditandai oleh interaksi antara mobilitas, ekspresi diri, dan adaptasi lingkungan. Meskipun mengalami pertumbuhan, perlengkapan fotografi yang ada seringkali mengabaikan tantangan kontekstual yang dihadapi oleh fotografer outdoor, termasuk cuaca tropis yang tidak menentu dan tuntutan gaya hidup digital yang mobile. Penelitian ini mengatasi kesenjangan tersebut dengan merancang tas kamera modular menggunakan pendekatan Human-Centered Design (HCD), dengan metode kualitatif berupa wawancara, observasi lapangan, dan kuesioner yang melibatkan fotografer outdoor urban. Proses desain mengikuti kerangka kerja HCD IDEO, yang terdiri dari tahap inspirasi, ideasi, dan implementasi, serta didukung oleh analisis tematik data lapangan untuk menghasilkan wawasan desain yang aplikatif. Desain akhir menitikberatkan pada fleksibilitas ruang, material tahan cuaca, dan modularitas untuk mendukung keberlanjutan dan personalisasi pengguna. Selain memenuhi aspek fungsional, tas ini berfungsi sebagai artefak budaya yang mewujudkan identitas visual serta merundingkan hubungan antara mobilitas digital, kondisi lingkungan, dan ekspresi budaya. Penelitian ini memberikan kontribusi dalam memperluas kerangka desain produk yang responsif secara budaya dengan mengintegrasikan dimensi sosial-budaya dan lingkungan, serta menjadi model inovasi berkelanjutan dalam konteks lanskap sosio-visual Indonesia.